Evaluation of atomic oxygen effects on nano-coated carbon-carbon structures for re-entry applications. (August 2019) - Delfini, A.; Santoni, F.; Bisegna, F.; Piergentili, F.; Pastore, R.; Vricella, A.; Albano, M.; Familiari, G.; Battaglione, E.; Matassa, R.; Marchetti, M.
Abstract: Since the beginning of Space Age, the re-entry phase represents a crucial task for both manned and unmanned aerospace missions. Along with high temperatures and plasma created by the spacecraft/atmosphere dramatic interaction, several issues must be considered in order to use new technologies and materials for re-entry systems. In particular, the effects of space environment due to ultraviolet (UV) and atomic oxygen (AO) have to be taken into account, in order to design and realize aerospace structures useful also for long duration missions. Such damaging factors, in fact, affect the spacecraft outer surfaces by degrading the thermo-mechanical properties of the materials designed to withstand re-entry conditions, thus frustrating their specific effectiveness. Carbon/Carbon (C/C) composites are widely used for high temperatures applications, including Thermal Protection Systems (TPS) for re-entry vehicles. In this work, a treatment of artificial aging was performed over in-house produced C/C material by means of AO ground facility at the Aerospace Systems Laboratory (LSA) of Sapienza University of Rome, evaluating erosion rate and surface oxides creation due to UV + AO irradiation. The experimental test was carried out setting the AO generator at a fluence of 8.7 × 10 20 atoms/cm 2, for an exposure time of 3000 equivalent sun hours. The material involved was manufactured by a customized vapor infiltration process; moreover, a protective coating was applied by using an aluminum oxide varnish charged with silicon di-oxide nano-spheres. The effect of coating is established by comparing with the results obtained for the uncoated material; an insight about the coating degradation due to the exposure is then assessed by morphological and chemical analyses. Highlights: Preserve re-entry C/C structures by coating is mandatory for aerospace missions. A novel coating treatment by alumina varnish and silica nanoparticles is proposed. Coated C/C samples are tested in AO-UV conditions typical of space environment. The effectiveness of the coating process in protecting the substrate is assessed. Oxidative/erosion effects are detailed by advanced spectroscopic analyses.